PENERAPAN ILMU KOMUNIKASI DAN PSIKOLOGI DALAM PROSES DAKWAH PENGARUHNYA TERHADAP PENGAMALAN AGAMA MASYARAKAT DI KECAMATAN PADANGSIDIMPUAN SELATAN - Harahap, Hamlan (Institut Agama Islam Negeri Padangsidimpuan, 2014)
AbstractThis research aim to know how big influence of applying of science of communications and psychology in course of mission of either through separate and also by simultan to deed of society religion. Counted 120 society people of taken as sampel by using technique of Cluster Sampling. Data collecting done to pass the kuesioner. Hereinafter data gathered to be analysed by using statistical and descriptive statistical analysis of inferensial. From the analysis result known by that applying of its influence communications science is very strong to religion deed that is 0.929. So also with the its influence psychology applying is very strong to religion deed that is 0.880, is hereinafter seen from both the variable by simultan have an effect on the strength to religion deed of equal to 0,939. From data analysis obtained by result of applying of communications science have an effect on positive and signifikan to deed of society religion in District of Padangsidimpuan South that is 27,339 > 1,659. So also psychology applying have an effect on positive and signifikan to religion deed that is 20,114 > 1,659. Hereinafter by simultan both the variable of positive influence and signifikan to religion deed that is 437,897 > 3, 08.Kata-kata Kunci: penerapan, ilmu komunikasi, psikologi, pengamalan agama.